Advances in the Application of Polymers of Intrinsic Microporosity in Liquid Separation and Purification: Membrane Separation and Adsorption Separation. (26th April 2021) - Ye, Hong; Zhang, Caili; Huo, Chaowei; Zhao, Bingyu; Zhou, Yuanhao; Wu, Yichen; Shi, Shengpeng
Abstract: Polymers of intrinsic microporosity (PIMs) are a new type of polymer material with unique microporous structure and have been widely applied in gas separation. In recent years, PIMs have also experienced rapid growth in liquid separation and purification; however, so far, no review is reported on the application of PIMs in this field. This paper reports a comprehensive and critical review on the recent research progress of PIMs in the application of liquid separation and purification including membrane separation and adsorption. First, the structural characteristics and synthesis methods of PIMs are briefly described. Subsequently, their applications in membrane separation are described in detail, including pervaporation (removal of organics from water, dehydration of solvents, and separation of organic mixtures), nanofiltration (dye rejection), and adsorption (dyes, organic contaminants, metal ions, oil/water separation, and enantiomeric separation). The effect of material structure and modification on the separation performance is emphasized, and possible new research directions are mentioned. Finally, the application of PIMs in liquid separation and purification is prospected. In conclusion, PIMs exhibit excellent separation efficiency and stable operation characteristics in liquid separation and purification, and they have attractive and broad development prospects. More valuable applications remain to be developed.